2016
DOI: 10.1371/journal.pone.0164800
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Large-Scale Social and Behavior Change Communication Interventions Is Associated with Improvements in Infant and Young Child Feeding Practices in Ethiopia

Abstract: Optimal breastfeeding (BF) practices in Ethiopia are far below the government’s targets, and complementary feeding practices are poor. The Alive & Thrive initiative aimed to improve infant and young child feeding (IYCF) practices through large-scale implementation of social and behavior change communication interventions in four regions of Ethiopia. The study assessed the effects of the interventions on IYCF practices and anthropometry over time in two regions–Southern Nations, Nationalities and Peoples Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 23 publications
3
149
0
2
Order By: Relevance
“…The trial aimed to deliver the MNP locally branded as Desta and infant and young child (IYC) feeding BCC activities to approximately 71,000 children 6–23 months in six woredas in Amhara Region (Kobo, Gubalafto, Delanta, Dessie Zuria, Kalu and Bati) and five woredas in Tigray Region (Saesi Tsaedaemba, Mereb Lehe, Werie Lehe, Gulomahda and Ahferom). The distribution of Desta was integrated into the IYC feeding BCC strategy developed by Alive & Thrive and implemented through the MOH's Health Extension Program (Kim et al, , ). The MOH, Concern Worldwide and Global Alliance for Improved Nutrition created guidelines, a training manual, job aids and materials for caregivers, which included information on the composition and purpose of Desta , instruction on food preparation with Desta and contraindications and potential side effects of Desta (see Table SS1 in the supporting information for key messages regarding Desta that HEW and health centre workers were trained to provide to caregivers).…”
Section: Methodsmentioning
confidence: 99%
“…The trial aimed to deliver the MNP locally branded as Desta and infant and young child (IYC) feeding BCC activities to approximately 71,000 children 6–23 months in six woredas in Amhara Region (Kobo, Gubalafto, Delanta, Dessie Zuria, Kalu and Bati) and five woredas in Tigray Region (Saesi Tsaedaemba, Mereb Lehe, Werie Lehe, Gulomahda and Ahferom). The distribution of Desta was integrated into the IYC feeding BCC strategy developed by Alive & Thrive and implemented through the MOH's Health Extension Program (Kim et al, , ). The MOH, Concern Worldwide and Global Alliance for Improved Nutrition created guidelines, a training manual, job aids and materials for caregivers, which included information on the composition and purpose of Desta , instruction on food preparation with Desta and contraindications and potential side effects of Desta (see Table SS1 in the supporting information for key messages regarding Desta that HEW and health centre workers were trained to provide to caregivers).…”
Section: Methodsmentioning
confidence: 99%
“…In Bangladesh, the intervention consisted of outreach-based home counseling delivered by a nongovernmental organization (15). In Ethiopia, the CF counseling was delivered by outreach-focused governmental health system workers (16). In Vietnam, a health facility–based counseling approach was used.…”
Section: Introductionmentioning
confidence: 99%
“…Mass media (MM) and community mobilization (CM) were used in all 3 countries to complement interpersonal counseling (IPC). Thus far, these studies have shown varying, but positive, impacts on breastfeeding in all 3 contexts (16, 17) and on CF in Bangladesh and Ethiopia (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…Mothers and couples need ongoing counseling to reinforce continued use of new practices and the adoption of other new practices as they and their children reach new milestones. Nutrition outcomes have improved as exposure to counseling messages increased in community-based nutrition programs (BASICS, 2008;Kim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the integration of FP and MIYCN information and services has numerous potential benefits, FP and MIYCN services are generally not offered together. Thus, opportunities for intensive interpersonal counseling for both FP and MIYCN, which has been shown to improve the uptake of health and nutrition practices, are being missed (Kim et al, 2016). The researchers sought to use research findings to identify successful strategies for increasing exposure to information about and uptake of optimal practices through integrated MIYCN and FP services, which has not been widely documented in the literature.…”
Section: Introductionmentioning
confidence: 99%